Implementation Of The Jigsaw Cooperative Learning Model In Increasing Elementary School Students' Learning Participation - Nurul Wahidiyatul Ma'rifah; Khurin In Ratnasari (APPLICATION: Applied science in Learning Research, 2026)
This study aims to describe the procedure for implementing the Jigsaw cooperative learning model to increase fourth-grade students' participation in learning. Learning participation is very important in the teaching/learning process at the elementary school level, because it shows students' active participation in the mental, emotional, and social aspects of the learning process. This study used a qualitative descriptive method to investigate the existing situation. The subjects of the study were teachers and fourth-grade elementary school students, data were collected through direct observation and in-depth interviews, as well as documentation. The data analysis process was carried out using the interactive analysis model, this model includes the stages of data collection, data condensation, data presentation, and drawing conclusions. The data were considered valid because of three different validation techniques and three different validation sources. The research findings indicate that the implementation of the Jigsaw model can increase student participation in learning, as evidenced by an increase in the number of questions asked and answers given, an increase in the number of opinions expressed, an increase in the number of groups formed, and the ability to collaborate. In addition, this model reduces the amount of power held by certain students while encouraging greater participation from all group members. The results show that the Jigsaw cooperative learning model is considered very important and useful for increasing the participation of elementary school students in learning